Speech text of the 2nd Chartered Management Institute (CMI) certification ceremony 2023 / Prof. Datuk Ts. Dr. Roziah Mohd Janor - Mohd Janor, Roziah (2023)
Alhamdulillah, with gratitude to the Almighty, we gather here tonight for the 2nd Chartered Management Institute (CMI) Certification ceremony dedicated to the Faculty of Business and Management – Master of Human Resource Management students. It is an honour to be part of this momentous occasion and to welcome over 40 individuals who are about to receive the prestigious CMI Certification.